Cisco IP telephony : planning, design, implementation, operation, and optimization - Kaza, Ramesh (Cisco Press networking technology series., 2005)
A guide to successful deployment of the Cisco IP Telephony solution Real-world case studies from the Cisco design consulting engineers who developed the PDIOO process provide practical advice on all stages of successful IPT deployment Concise understanding of the PDIOO phases enables architects and engineers to successfully deploy the Cisco IPT solution Division of the process into PDIOO phases provides a logical and defined guide for network engineers and architects as they proceed through each of the phases in deploying the Cisco IPT solution Includes detailed questionnaires for each phase of deployment in the PDIOO cycle-a great aid in understanding customer networks and requirements Network infrastructure design, call processing infrastructure design and applications, and voice-mail system design are covered in depth Cisco® IP Telephony (IPT) solutions are being deployed at an accelerated rate, and network architects and engineers need to understand the various phases involved in successful deployment: planning, design, implementation, operation, and optimization (PDIOO). On the road to that understanding, those involved need to collect information for each phase of deployment, and then follow through with the best architecture, deployment model, and implementation based on the data collected. Cisco IP Telephony: Planning, Design, Implementation, Operation, and Optimization is a guide for network architects and engineers as they deploy the Cisco IPT solution. With this book, you will master the PDIOO phases of the IPT solution, beginning with the requirements necessary for effective planning of a large-scale IPT network. From there, you'll follow a step-by-step approach to choose the right architecture and deployment model. Real-world examples and explanations with technical details, design tips, network illustrations, and sample configurations illustrate each step in the process of planning, designing, implementing, operating, and optimizing a chosen architecture based on information you have collected. In-depth instruction on each PDIOO phase provides specific details about the tasks involved and best practices for successful implementation of the IPT solution. This book also contains predesigned questionnaires and PDIOO assistance tools that help you determine the requirements of each phase of the PDIOO cycle. Authors Ramesh Kaza and Salman Asadullah have been involved with Cisco IPT solutions from the beginning and have planned, design...